EXPLORATION OF MULTICULTURAL APPROACHES IN HISTORY LEARNING IN MULTIETHNIC CONTEXTS: CASE STUDY AT SMAN 14 MEDAN - Br Manalu, Dewi Ningsih; Diansyah, Arfan; Gultom, Imelda Megawati (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This research aims to explore a multicultural approach to teaching history at SMAN 14 Medan, especially in a multiethnic context. The multicultural approach here refers to the integration of various ethnic perspectives into the history curriculum to increase understanding and respect for cultural diversity. This study was conducted using qualitative methods and data collection techniques through classroom observations, interviews and document analysis. The research results show that the application of a multicultural approach to history learning at SMAN 14 Medan has helped students understand and appreciate cultural differences, as well as increasing student involvement in the learning process. Key success factors include teacher training, teaching materials relevant to multiethnic contexts, and an inclusive learning atmosphere. The implication of this research is the importance of applying a multicultural approach to history learning to enrich students' learning experiences in a multiethnic context. It is hoped that this research can contribute to the development of a more inclusive history curriculum in ethnically diverse schools. By understanding and appreciating cultural diversity, students are equipped with the skills necessary to interact effectively in a multiethnic environment. Teachers, as facilitators, have a key role in creating a supportive learning environment for all students, thereby creating valuable and relevant learning experiences. This research also highlights several limitations, such as the research being limited to one school and the qualitative approach used. Therefore, further research involving a number of schools and using quantitative methods can provide a broader understanding of the effectiveness of a multicultural approach in teaching history.Applying a multicultural approach to history learning not only benefits students academically but also helps prepare them to live and work in an increasingly multicultural society. Thus, inclusive and multicultural history learning is not only relevant in an educational context but is also important for building an inclusive and tolerant society in the future.